Ibu Hamil dengan Tingkat Kecemasan dalam Menghadapi Persalinan di Puskesmas Sudiang Kota Makassar - Ekawati, Nur; Djunaedi, Djunaedi; Kurniawati, Kurniawati; Rosida, Rosida; Thalib, Kiki Uniatri; Wahyudianti, Ni Luh Gede Sri (Barongko: Jurnal Ilmu Kesehatan, 2023)
Government efforts to accelerate the reduction of maternal and infant mortality through increasing knowledge and changing the behavior of mothers and families. With this increase in knowledge and behavior change, it is hoped that awareness of the importance of health during pregnancy will become a program organized by the ministry of health to support this step, namely the class for pregnant women, class activities for pregnant women, class activities for pregnant women using learning methods, one of which is the discussion of MCH book material. improve the quality of maternal and child health services and nutrition so that one of the national development goals, namely reducing MMR and IMR, is achieved. The purpose of this study was to determine the anxiety level of pregnant women in facing childbirth at the Sudiang Makassar Health Center. This research uses a descriptive analytic research method which is a method that functions to describe or give an overview of the object under study through collected data or samples, with a Cross Sectional approach. The results of this study are grouped into two, namely Univariate Analysis and Bivariate Analysis which will be presented in tabular form to see the relationship between the dependent and independent variables, using the Chi-square statistical test with a significance level of α = 0.05 it is said to be significant if it is said to be significant if ρ < 0.05 means that there is a relationship between the two variables, and is said to be insignificant if ρ ≥ 0.05 means that there is no relationship between the variables.